Microbial Biofilms in the African Plastisphere Implications for Freshwater Ecosystems and Contaminant Degradation - Xu, Lei; Hong, Ziming (My University, 2024)
Microbial biofilms on plastic debris, collectively known as the plastisphere, play a dual role in Africa’s freshwater ecosystems. These biofilms contribute to nutrient cycling and contaminant degradation, yet they also serve as potential vectors for pathogens and antibiotic resistance genes. Plastic waste in aquatic systems disrupts microbial communities, raising concerns over water quality and ecosystem health. Biofilm adaptability enhances pollutant breakdown, particularly for heavy metals and organic contaminants, while simultaneously increasing environmental contamination risks. This study emphasizes the need for further research to manage biofilm interactions with plastic pollution, addressing critical ecological challenges in Africa's freshwater environments.
Keywords: microbial biofilms; plastisphere; freshwater ecosystems; contaminant degradation; antibiotic resistance genes; Africa; plastic pollution; ecosystem health; nutrient cycling; bioremediation